2020
DOI: 10.21203/rs.2.20901/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of early neuraminidase inhibitor therapy on clinical outcomes in patients hospitalised with influenza A-related pneumonia: a multicenter, retrospective study

Abstract: Background Guidelines emphasize prompt antiviral treatment in severe influenza patients. Although nearly a 50% of severe influenza present with pneumonia, the effect of early (≤ 2 days after illness onset) neuraminidase inhibitor (NAI) use on the clinical outcomes of influenza A-related pneumonia (FluA-p) has rarely been assessed. Furthermore, data about the administration of NAIs in the real-world management of Flu-p in China are limited.Methods: Data of patients hospitalised with FluA-p from five teaching ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Impaired pulmonary function and the retention of carbon dioxide in the lungs can further drive respiratory acidosis, leading to higher rates of NIMV failure and an increased risk of requiring IMV [29]. Many observational studies showed inhibiting viral replication at early time points can reduce virus-induced in ammation and tissue damage, thereby decreasing overall in uenza-related mortality rates [30][31][32]. Our data also suggest that early NAI treatment was associated with a lower risk of Flu-p patient intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired pulmonary function and the retention of carbon dioxide in the lungs can further drive respiratory acidosis, leading to higher rates of NIMV failure and an increased risk of requiring IMV [29]. Many observational studies showed inhibiting viral replication at early time points can reduce virus-induced in ammation and tissue damage, thereby decreasing overall in uenza-related mortality rates [30][31][32]. Our data also suggest that early NAI treatment was associated with a lower risk of Flu-p patient intubation.…”
Section: Discussionmentioning
confidence: 99%